Dinamisasi manajemen mutu presfektif pendidikan Islam - Rizky Setyawan, Dimas Yon (Maliki Interdisciplinary Journal, 2024)
The aim of this research is to provide insight into the dynamics of quality management or educational views to readers, observers, academics and educational practitioners to understand how comparisons can be made from various angles and with public awareness of the importance of education, it is hoped that the quality of education in Indonesia can be better. and continues to develop and improve. This raises the research question of how to develop education quality management in the era of regional autonomy and educational autonomy through the application of management principles with an educational paradigm. The results of this research are improving quality through optimization. The functions and objectives of standardization are (1) National Education Standards function as a basis for planning, implementing and supervising education in order to realize quality national education, (2) National Education Standards aim to guarantee the quality of national education. in order to educate the nation's life and form a dignified national character and civilization, (3) National Education Standards are refined in a planned, directed and sustainable manner in accordance with the demands of changes in local, national and global life and the impact of the results of basic education development on regional autonomy.